A comprehensive assessment of benign genetic variability for neurodegenerative disorders - Guerreiro, Rita; Sassi, Celeste; Gibbs, Jesse; Edsall, Connor; Hernandez, Dena; Brown, Kristelle; Lupton, Michelle; Parkinnen, Laura; Ansorge, Olaf; Hodges, Angela; Ryten, Mina; Tienari, Pentti; et al. (2018)
Over the last few years, as more and more sequencing studies have been performed, it has become apparent that the identification of pathogenic mutations is, more often than not, a complex issue. Here, with a focus on neurodegenerative diseases, we have performed a survey of coding genetic variability that is unlikely to be pathogenic. We have performed whole-exome sequencing in 478 samples derived from several brain banks in the United Kingdom and the United States of America. Samples were included when subjects were, at death, over 60 years of age, had no signs of neurological disease and were subjected to a neuropathological examination, which revealed no evidence of neurodegeneration. This information will be valuable to studies of genetic variability as a causal factor for neurodegenerative syndromes. We envisage it will be particularly relevant for diagnostic laboratories as a filter step to the results being produced by either genome-wide or gene-panel sequencing. We have made this data publicly available at www.alzforum.org/exomes/hex.